Enhancing immunity to nematode parasites in single-bearing Merino ewes through nutrition and genetic selection - Kahn, L.P.; Knox, M.R.; Gray, G.D.; Lea, J.M.; Walken-Brown, S.W. (Elsevier, 2003)
The effectiveness of protein supplementation and genetic selection to enhance the resistance of periparturient Merino ewes to infection from gastrointestinal parasites was tested in a replicated grazing experiment. One hundred and twenty ewes from lines selected for increased resistance (R) to Haemonchus contortus or at random (C) were subjected to one of the three supplement groups that provided 0 or 250 g per day cottonseed meal for 5 weeks prior to, or for 6 weeks after the start of lambing. Faecal egg counts (FEC) of R ewes were consistently lower than those of C ewes but both groups exhibited a periparturient rise in FEC. Supplementation during the pre-partum period reduced FEC and increased ewe body weight gain. The benefits of pre-partum supplementation in reducing FEC continued to be apparent up to 10 weeks after supplementation ceased. There was a strong suggestion that the benefits to parasite resistance from protein supplementation were greatest in C ewes. Wool growth rates (15%) and birth weights (5%) were greater for C ewes but differences between the lines for lamb body weight had disappeared by day 97. The greatest benefit to resistance from protein supplementation was observed when ewes were experiencing a loss of maternal body weight. Conversely, no benefits to resistance were observed when ewes had moderate (78–107 g per day) rates of maternal weight gain. These results suggest that increased resistance as a result of protein supplementation is dependent on the prevailing supply and demand for scarce nutrients such as metabolisable protein (MP). Both genetic selection and protein nutrition are effective strategies to enhance host resistance to nematode infection during the periparturient period.